Project-Based Learning and Numeracy Literacy in Vocational Education: A Systematic Review of Their Impact on Critical Thinking - Waode Husriawati; Nila Ubaidah (Jurnal Didactical Mathematics, 2026)
Despite growing interest in fostering critical thinking in mathematics education, existing studies tend to examine pedagogical approaches, cognitive competencies, and digital tools in isolation, resulting in a fragmented understanding of how these elements interact in vocational education contexts. This study addresses this gap by systematically synthesizing evidence on the interplay between Project-Based Learning (PBL), numeracy literacy, and digital tool integration in enhancing students’ critical thinking skills. A systematic literature review was conducted following the PRISMA framework, analyzing peer-reviewed articles indexed in Scopus, Web of Science, and ERIC published between 2015 and 2024. Studies were selected based on predefined inclusion criteria, including relevance to vocational education, explicit focus on critical thinking outcomes, and empirical or review-based evidence. A thematic synthesis approach was employed to identify patterns of interaction among pedagogical, cognitive, and technological dimensions. The findings reveal that PBL functions as the primary pedagogical driver structuring inquiry-based learning, while numeracy literacy serves as a cognitive mediator, enabling students to process, interpret, and apply mathematical reasoning. Digital tools, in turn, act as facilitating instruments that enhance engagement and support iterative problem-solving processes. The interaction of these three elements forms a complementary system that significantly strengthens the development of critical thinking, rather than contributing independently. This study contributes by proposing an integrative conceptual perspective that explicates the synergistic relationship between instructional design, cognitive development, and technological support in vocational mathematics education. The findings offer a more coherent framework for understanding how critical thinking can be systematically fostered through aligned pedagogical and technological practices.